Gestão de pessoas na administração pública - Moraes, Roger da Silva (2023)
This article focuses on people management in public administration. In this way, the article will answer the following question: What are the main challenges of people management in public administration? Through quantitative research carried out with the Municipal Department of Finance and Inspection of the municipality of Soledade/RS. This research consists of applying a questionnaire consisting of 24 (twenty-four) multiple-choice questions, with only career employees selected, with the general objective of identifying the main challenges of people management in public administration, with the specific objectives: identifying which are the bottlenecks in the area of people management within the aforementioned secretariat through the application of a multiple choice questionnaire, analyzing the collected data and finally, proposing an action plan to control the bottlenecks found. From this analysis it will be possible to answer the research question, in order to seek an adequate and comprehensive solution, presenting an action plan that is beneficial to employees so that they can resolve the bottlenecks found, making the work environment more harmonious. and the most valued servant given the role he performs.